DeteÂ· rmination of 6 -Mixing Ratios of yÂ Transitions From Levels of llo, 112 u 4 Cd populated in The 110 112 ’ 114 Cd (n,Ii y) Reactions - Snid, B . M.; Yonbana, H.M.; Hadeed, W.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
L The o - mixing. ratios of y- transitions from level of 1 Hi. 11 - 1 4 Cd populated in the 1 H1â€¢ 112 11 4 Cd (n,n ’Y) reactions .have beeh cakulated in the present work u_ ing the .2- rati9 method. The results. obtained confirm the validit)l of this m’ethod and its cÂ·pab.ility i.n predicting any inaccuracy in the expe.[imental data.